Beyond good boys and nice girls: Unpacking Childhood Ideologies of Indonesian Peaceful Islam - Ali Formen; Naili Rohmah; Renistiara Medilianasari; Wantoro Wantoro (Universitas Pesantren Kh abdul Chalim Mojokerto, 2026)
This article examines how contemporary Indonesian stories of peaceful Islam construct ideas of the “good” Muslim child, focusing on the Rahmatan Series children’s books. It explores at how these books shape children’s moral subjectivities and whether they in support of the broader campaigns fostering moderate, peaceful Islam. Using Critical Discourse Analysis, the study identifies key moral themes, character roles, and ethical positions in the Series. Four dominant constructions of good Muslim children emerge: defenders of religious identity, pioneers of empathy and sacrifice, effective emotional self-regulators, and positive influencers. While the Series aims to promote peaceful Islamic values, the analysis reveals tensions, including the overrepresentation of female protagonists, the privileging of middle-class urban Muslim life, and the absence of non-Muslim moral exemplars. Theoretically, the study contributes to childhood and religious education scholarship by showing how peace-oriented narratives may simultaneously challenge and perpetuates stereotypes and biases. Practically, the findings offer insights for authors, educators, and policymakers, highlighting the need for socially inclusive and gender-balanced narratives. In alignment with SDG 4 (quality education) and SDG 16 (peace and justice), the article calls for Islamic children’s literature that more fully reflects diversity, equity, and interfaith coexistence.